Leader Member Exchange and Knowledge Sharing on Innovative Work Behavior with Work Engagement as a Mediating Variable - Ulfatmi, Alda; Sulastri, Sulastri (Human Resource Management Studies, 2023)
The purpose of this study was to analyze the relationship between leader member exchange, knowledge sharing and innovative work behavior when work engagement is a mediating variabel to employee PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur. The population in this study were all employee in the PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur as many as 124 employees. The number of samples unsed in the study was 122 employees using the proportional cluster simple random sampling technique. The research design used in this study is causative research. The data analysis technique used is the Structural Equational Model (SEM) with the help of the SmartPLS 3.3 The results of this study revealed that: (1) Leader member exchange has a significant effect on innovative work behavior. (2) The influence of leader member exchange has a significant effect on work engagement. (3) Knowledge sharing has a significant effect on innovative work behavior. (4) The influence of knowledge sharing has a significant effect on work engagement. (5) The influence of work engagement on work engagement. (6) work engagement mediating the leader member exchange and innovative work behavior. (7) work engagement mediating the knowledge sharing and innovative work behavior to employee at the PT Pelabuhan Indonesia (Persero) Regional 2 Teluk Bayur.